Academic Writing Challenges and Encouragements: Perspectives of University Teachers in Far Western University - Khati, Ashok Raj (Far Western Review, 2024)
While academic writing skills constitute a central place in master’s level courses at universities, institutional support for students has often been lacking. As a result, students face challenges in producing scholarly writing. In this study, I attempted to explore the academic writing challenges and encouragements to enhancing academic writing of master’s level students from the perspectives of university teachers at Far Western University of Nepal. This is a qualitative study. The data were collected through semi-structured interviews. Five university teachers from three different disciplines were selected as the research participants. The study shows that students’ awareness of academic writing is very low. Additionally, the traditional role of supervisors has negative effects on students’ academic writing. The study, however, reveals that training, workshops, virtual seminars and individual feedback have contributed to improving their academic writing. The study concludes that there is no adequate provision for research, and the university does not seem to have visible policies and plans for developing students’ academic writing.